Upaya Bandara Ngurah Rai Denpasar Dalam Mewujudkan Safety Management System (SMS) - Muliasari, Ataline (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Each airport management including Denpasar Ngurah Rai International Airport are required tocreate, implement, eunluate and impmue the sustainnble safe ; rruznagement si;stem (SMS) with asafehJ program based on intemntionnl mzd nntionnl flight s. Relnted to the nhaue, ns nn internationalairport located in the center of touris111 lcxatio11 of hzdonesin, Nguralt Rni lntenuztional Airport tnjingto realize its SafehJ Management System (SMS). Ihis condition is certainly important to be realizedconsidering the level of aircraft mauements for both international and national flights is very high atthis airport. Vvhen considering the results of a questionnaire on the indicators of Hazard Identifica.tionand Risk Management, there are variables that are in the position of